Physiology of digestive system - Sukhomlinova, I. Ye.; Kushch, O. G.; Tykhonovska, M. A.; Morozova, O. V.; Chugin, S. V.; Yeryomina, A. K.; Krashevskyi, A. V.; Putilin, D. A.; Сухомлінова, Ірина Євгенівна; Кущ, Оксана Георгіївна; Тихоновська, Марина Анатоліївна; Морозова, Оксана Валентинівна; et al. (Zaporizhzhia state medical university, 2017)
This electronic manual is recommended for II year students of International Faculty of specialty "General medicine" studying biological chemistry, as additional material to prepare for practical training semantic modules 13 of module 2 and licensing exam "KROK 1: General medical training".
Фізіологія травної системи